1986
DOI: 10.1016/0035-9203(86)90393-7
|View full text |Cite
|
Sign up to set email alerts
|

Total dose iron infusion, malaria and pregnancy in Papua New Guinea

Abstract: A study was made of 544 mothers and their 556 newborns in an area of endemic malaria, to analyse effects of total dose intravenous iron infusion (TDI) to mothers during pregnancy. 34% of these mothers received TDI before delivery. A range of haematological tests was carried out on newborns and mothers in addition to anthropometry. 84% of mothers had had ante-natal care and data were also collected retrospectively from ante-natal records. TDI was associated with more slide positive peri-natal malaria in primipa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 4 publications
1
25
0
Order By: Relevance
“…It must be pointed out also that there is evidence that administration of parenteral iron to iron-deficient women during pregnancy in malaria-endemic areas may be associated with an increase in the incidence of malarial infections and clinical episodes of disease. 170,171 Thus, care must be exercised in administering iron supplements alone (without chemoprophylaxis) in malaria-endemic areas.…”
Section: Iron Supplementationmentioning
confidence: 99%
“…It must be pointed out also that there is evidence that administration of parenteral iron to iron-deficient women during pregnancy in malaria-endemic areas may be associated with an increase in the incidence of malarial infections and clinical episodes of disease. 170,171 Thus, care must be exercised in administering iron supplements alone (without chemoprophylaxis) in malaria-endemic areas.…”
Section: Iron Supplementationmentioning
confidence: 99%
“…Regardless of the beneficial effect of iron/folic acid supplements, there have been reports of an adverse effect of iron supplements on malaria infections in children (16) and pregnant women living in malaria-endemic areas (17). In these studies, the rate of malaria infections was reported to increase in women and children who received iron (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 97%
“…In these studies, the rate of malaria infections was reported to increase in women and children who received iron (16)(17)(18)(19). However, a recent metaanalysis showed no evidence of adverse effects of iron treatment in children from endemic-malaria areas (20).…”
Section: Introductionmentioning
confidence: 97%
“…However, in endemic areas, malaria may be an equally important cause of anaemia, especially in primigravidae (BRABIN, 1983). Two studies have shown that parenteral iron administration during pregnancy increased susceptibility to malaria (BYLES & D'SA, 1970;OPPENHEIMER et al, 1986). We therefore carried out a controlled trial of iron supplementation in pregnant women resident in a rural area of The Gambia where malaria is common.…”
Section: Introductionmentioning
confidence: 99%